Tingkat Pengetahuan PUS tentang KB dengan Coitus Interuptus di Wilayah Polindes Desa Tiwet Kecamatan Kalitengah Kabupaten Lamongan - Sujianto, Sujianto (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2009)
This research analyzes about level of knowledge fertility age couple (PUS) about family planning with method coitus interuptus in region Polindes Countryside Tiwet District Kalitengah Sub-Proovince Lamongan. Method applied by quota sampling with responder 30 PUS. Result of research shows level of knowledge obtained is medium that is 13 responders (43%), level of low knowledge with 12 responders (40%), level of high knowledge of 5 responders (17%)Keyword: level of knowledge, fertility age couple (PUS), methode coitus Interuptus